(untitled) (Journal of Oriental Studies, 2018)
This article is considered the defining characteristics of translation of fictions from Turkish into Kazakh. Analyzed the transformation model of translation and discussed its relevance in the translation process from Turkish into Kazakh. Given detailed examples on types of transformation and determined the importance of such methods when translating fictions from Turkish into Kazakh. Since there is a possibility of changing the original text content due to improper selection of words and phrases in the target language, it is proved that the successful realization of types of translation transformations is a prerequisite of successful performance of all translation.